2022
DOI: 10.1186/s12913-022-08546-6
|View full text |Cite
|
Sign up to set email alerts
|

The relative impact of underweight, overweight, smoking, and physical inactivity on health and associated costs in Indonesia: propensity score matching of a national sample

Abstract: Background Indonesia is in the middle of a rapid epidemiological transition with an ageing population and increasing exposure to risk factors for chronic conditions. This study examines the relative impacts of obesity, tobacco consumption, and physical inactivity, on non-communicable diseases multimorbidity, health service use, catastrophic health expenditure (CHE), and loss in employment productivity in Indonesia. Methods Secondary analyses were conducted of cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 28 Furthermore, the Indonesian Family Life Survey 2014/2015 (12,081 participants) has shown that being overweight to obese and actively smoking tobacco are associated with elevated incidence of chronic multimorbidity (p < 0.05), particularly involving non-communicable diseases such as hypertension, T2DM, stroke, and ischemic heart disease. 29 Another study has indicated an association between very high BMI and a 2.7-fold higher risk (95% CI: 2.1–3.3) of mortality due to atherosclerosis-associated diseases. 30…”
Section: Discussionmentioning
confidence: 98%
“… 28 Furthermore, the Indonesian Family Life Survey 2014/2015 (12,081 participants) has shown that being overweight to obese and actively smoking tobacco are associated with elevated incidence of chronic multimorbidity (p < 0.05), particularly involving non-communicable diseases such as hypertension, T2DM, stroke, and ischemic heart disease. 29 Another study has indicated an association between very high BMI and a 2.7-fold higher risk (95% CI: 2.1–3.3) of mortality due to atherosclerosis-associated diseases. 30…”
Section: Discussionmentioning
confidence: 98%
“…From the Scopus database, 21 articles about communications and successful aging were published and indexed from 2015–2022. However, in the Indonesian context, the publications related to aging in 2022 were about health [ 20 , 21 , 22 , 23 ], quality of life [ 24 , 25 ], construction of policy [ 26 , 27 ], public bathroom design [ 28 ], macro-demographics [ 29 ], gross saving [ 30 ], somatosensory stimulation [ 31 ], intergenerational support [ 32 ], and pension [ 33 , 34 ]. As of 27 November 2022, there was no specific aging study from a communications perspective, especially from communications scholars.…”
Section: Introductionmentioning
confidence: 99%